PENYELESAIAN PAILIT DI BMT YOGYAKARTA: STUDI KASUS DI BMT SABILUL MUHTADIN DAN BMT AL-MUTHI’IN BANGUNTAPAN BANTUL, YOGYAKARTA - Suaidi Suaidi (Nurul Jadid University, 2019)
The issue of brankrupt BMT is problematic since its settlement deals with a dilemma in which the goverment is irresponsive to that issues and the protection of customers’ fund is necessary. It is important to have a regulation of legal protection upon the brankrupt small and medium enterprises, such as BMT, dealing with a fact that many BMTs are brankrupt without having a substitutive funds. This article depicts a condition in which two BMTs in Yogyakarta, BMT Sabilul Muhtadin and BMT Al-Muthi’in, are assumed as having brankrupty, and the ways both of them made a legal protection to their customers and had some ways of settlements of their rights after that brankrupt situation. Keywords: Protection, Baitul Maal wat-Tamwil, Brankrupty